EPISTEMOLOGI DALAM FILSAFAT ILMU: Tinjauan Historis, Konseptual, Metodologis, dan Aliran-Aliran Pemikiran dalam Konteks Pendidikan Dasar - Selly Noverina; Margaretha Herlin Pratiwi; Alda Permatasari; Annasriyah Masfufah; Novi Lestari; Darwin Effendi; Hasperi Susanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine epistemology as a fundamental pillar in the philosophy of science, particularly within the context of primary education practice development. Four major dimensions are addressed comprehensively: the nature and position of epistemology in the structure of philosophy of science, a reconstruction of the history of knowledge from ancient civilizations to the postmodern era, the conceptualization of scientific knowledge along with the scientific method's procedures and structural hierarchy, and a critical mapping of epistemological schools from rationalism, empiricism, criticism, pragmatism, positivism, phenomenology, to constructivism. Unlike previous studies that tend to examine these dimensions separately, this research integrates them into a unified analytical framework relevant for primary education practitioners and policymakers. The method employed is a systematic literature review with a hermeneuticphilosophical approach. Findings reveal a significant gap in Indonesianlanguage literature concerning the application of epistemology in primary education contexts. This article contributes by offering an integrated epistemic framework as a guide for curriculum development and scientifically grounded instruction.